2020
DOI: 10.1038/s41398-020-00897-0
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, double-blind, active placebo-controlled study of efficacy, safety, and durability of repeated vs single subanesthetic ketamine for treatment-resistant depression

Abstract: The strategy of repeated ketamine in open-label and saline-control studies of treatment-resistant depression suggested greater antidepressant response beyond a single ketamine. However, consensus guideline stated the lack of evidence to support frequent ketamine administration. We compared the efficacy and safety of single vs. six repeated ketamine using midazolam as active placebo. Subjects received either six ketamine or five midazolam followed by a single ketamine during 12 days followed by up to 6-month po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 47 publications
(54 reference statements)
2
48
0
Order By: Relevance
“…34 Interestingly, all of these reports [31][32][33][34] describe attenuation of both acute and sustained effects of ketamine in MDD. While a recent study 35 did not replicate these findings, BZD doses were not reported. Since this may be a dosedependent effect, it is challenging to interpret the significance of this.…”
Section: Gaba Interneuronsmentioning
confidence: 78%
See 1 more Smart Citation
“…34 Interestingly, all of these reports [31][32][33][34] describe attenuation of both acute and sustained effects of ketamine in MDD. While a recent study 35 did not replicate these findings, BZD doses were not reported. Since this may be a dosedependent effect, it is challenging to interpret the significance of this.…”
Section: Gaba Interneuronsmentioning
confidence: 78%
“…BZDs have been reported [31][32][33][34] to attenuate the effect of ketamine in MDD. While not all studies have reported evidence of this interaction, 35 given the persistence of this effect in the setting of heterogeneous data and proposed mechanism of ketamine in MDD, it seems likely that BZDs pose a pharmacodynamic interaction in a dose-dependent manner. Limited data exists around ketamine and concomitant AEDs in MDD.…”
Section: Discussionmentioning
confidence: 99%
“…No participants met response criteria within four hours of the first infusion session in either group. There have been very few trials that have examined serial ketamine infusions in depressed patients and results have been inconsistent in terms of its potential to prolong its antidepressant effects [22][23][24] . As this is a pilot trial with a small number of participants, we were unable to establish differences in depression scores at the follow-up time points.…”
Section: Discussionmentioning
confidence: 99%
“…Results showed that ketamine was not superior over placebo in reducing depression scores. A very recent clinical trial (n=54) compared a single ketamine infusion (preceded by five midazolam (active placebo) infusions) to six repeated ketamine infusions in medicated participants with diagnosed treatment resistant depression 24 . Ketamine had a greater antidepressant effect over midazolam.…”
Section: Introductionmentioning
confidence: 99%
“…Because the antidepressant effects of ketamine are relatively transient, repeated doses are often required to maintain them. However, repeated doses may not produce markedly enhanced antidepressant effects than a single ketamine treatment [ 99 ].…”
Section: Ketamine As An Antidepressant Drugmentioning
confidence: 99%